2017
DOI: 10.1128/aac.02441-16
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions between Hepatitis B Virus RNase H Antagonists and Other Inhibitors

Abstract: Combination therapies are standard for management of human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections; however, no such therapies are established for human hepatitis B virus (HBV). Recently, we identified several promising inhibitors of HBV RNase H (here simply RNase H) activity that have significant activity against viral replication in vitro. Here, we investigated the in vitro antiviral efficacy of combinations of two RNase H inhibitors with the current anti-HBV drug nucleoside analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ]. In addition, Didierjean et al have reported that DNA polymerase activity of HIV-1 RT can be inhibited by structurally related 3,7-dHTs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ]. In addition, Didierjean et al have reported that DNA polymerase activity of HIV-1 RT can be inhibited by structurally related 3,7-dHTs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies demonstrated the potential of inhibiting the viral ribonuclease H strategy as a promising alternative for developing new anti-HBV drugs. Combinations of RNase H inhibitors with other antiviral agents had additive antiviral effects without enhanced cytotoxicity [ 159 ].…”
Section: New Direct-acting Antivirals For Hbvmentioning
confidence: 99%
“…The RNaseH inhibitors repress HBV RNaseHs from three genotypes, indicating that HBV's high genetic diversity is unlikely to complicate drug development [13]. The inhibitors are synergistic with the nucleoside analog drug Lamivudine and additive with the experimental HBV capsid protein assembly modifier Hap12 without enhancing cytotoxicity [10,14]. Two RNaseH inhibitors, an HPD (208) and an αHT (110), can significantly suppress HBV replication in chimeric mice carrying humanized livers [15].…”
Section: The Rnaseh As a Drug Targetmentioning
confidence: 99%
“…2). This is because HBV RNaseH inhibitors work synergistically with nucleoside analogs and additively with capsid assembly modifiers, are insensitive to HBV's genetic variation, and different chemotypes of RNaseH inhibitors can be synergistic with each other [10,14]. Developing such a battery of anti-HBV drugs may finally achieve the long-sought goal of achieving a functional cure for chronic HBV infections.…”
Section: Prospects For Rnaseh Drugs In Combination Therapiesmentioning
confidence: 99%